Effect of the inclusion of oregano essential oil in the diet of weaned piglets on productive parameters - Baca C., Nelson (2020)
The aim of this study was to evaluate the effect of the supplementation of essential oil of oregano on the productive parameters in weaned piglets. The study was carried out in a commercial pig farm in Ventanilla, Callao, Peru. The supplementation was for 12 days. One hundred and twenty piglets randomly allocated in 8 pens of 15 animals were distributed in two treatments: T1, control, with a pre-start diet with 18% protein, 600 ppm amoxicillin and 55 ppm carbadox; T2, diet as in T1 plus supplementation with 500 ppm of oregano essential oil (Origanum vulgare). The weight gain, feed consumption and feed conversion ratio were evaluated. A lower feed intake was found in T2 (1.58 kg) compared to T1 (1.84 kg) (p <0.05). The weight gain and the feed conversion index were not affected by the treatments.